(untitled) (Bloomington, 1979)
The project which led to publication of this book had as its purpose to produce and disseminate a body of descriptive material about the politics of food problems in a representative group of nations and the relation of those national political decisions to others taken at the international level. The study group established in early 1977 set out to shed light on the political determinants of food policies rather than on the technical soundness of those policies. The contributors to this volume have chosen to concentrate on the internal process of supplying food to malnourished populations in developing countries.
Keywords: Cung cấp thực phẩm,Food supply; Hội nghị,Congresses